2006
DOI: 10.1300/j021v26n02_06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy and Age Discrimination Between Psychology and Nursing Students

Abstract: This study considered two types of age discrimination (youth and elder) and related scale scores for 108 psychology students and 81 nursing students. The current study found that although the nursing students had a significantly larger number of courses related to aging, both nursing and psychology students reported low levels of age discrimination. Overall, attitudes of both the nursing and psychology students toward both young and elder populations were positive. Nursing students held higher levels of effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…In addition to positive attitudes (e.g. ), negative and neutral attitudes were also reported. When referring to ageing, students generally described physical attributes and defined ageing as a negative process .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to positive attitudes (e.g. ), negative and neutral attitudes were also reported. When referring to ageing, students generally described physical attributes and defined ageing as a negative process .…”
Section: Resultsmentioning
confidence: 99%
“…Of 175 student volunteers, 114 were first-grade students and 61 were fourth-grade students. The Personal Information Form and Ageism Attitude Scale (AAS), prepared by the researchers on the basis of the literature, were used for data collection (1,5,6,(8)(9)(10).…”
Section: Methodsmentioning
confidence: 99%
“…observed that both student groups had positive attitudes toward the elderly; however, it was later observed that psychology students had a stronger preference for working with the elderly than nursing students (9). Molye (10) determined that nursery education students did not want to work with the elderly and had a negative discrimination attitude.…”
mentioning
confidence: 99%
“…The other seven studies (Belinga, 2003;Cankurtaran et al, 2006;Holroyd, Dahlke, Fehr, Jung, & Hunter, 2009;Karlin, Emick, Mehls, & Murry, 2006;Plonczynski et al, 2007;van Zuilen, Rubert, Silverman, & Lewis, 2001;Wells et al, 2004) reported insufficient data to allow this analysis.…”
Section: Attitude Trend Difference Over Time Between Different Healthmentioning
confidence: 96%